2006
DOI: 10.1074/jbc.m602424200
|View full text |Cite
|
Sign up to set email alerts
|

Destruction of Pancreatic β-Cells by Transgenic Induction of Prostaglandin E2 in the Islets

Abstract: Type 2 diabetes mellitus is characterized by insulin resistance of peripheral tissues and dysfunction of pancreatic ␤-cells. Furthermore, the number of pancreatic ␤-cells decreases as a secondary effect of advanced type 2 diabetes, although the molecular mechanism has not been elucidated. Recently, it has been shown that hyperglycemic conditions induce the expression of cyclooxygenase-2 in pancreatic islets and increase the downstream product prostaglandin E 2 (PGE 2 ). To investigate whether high glucose-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 30 publications
2
41
0
Order By: Relevance
“…We have measured TNF-a protein levels in islets from fresh soyabean oil-or OFO-fed mice, but found no difference (data not shown). Since significantly higher levels of PGE 2 metabolites have been observed in the plasma and urine of OFO-fed rats (43) and increased PGE 2 expression in islets has been shown to result in the destruction of pancreatic islets (44) . The effect of oxidative stress, inflammation and apoptosis on b-cells and OFOinduced islet dysfunction awaits further study.…”
Section: Discussionmentioning
confidence: 99%
“…We have measured TNF-a protein levels in islets from fresh soyabean oil-or OFO-fed mice, but found no difference (data not shown). Since significantly higher levels of PGE 2 metabolites have been observed in the plasma and urine of OFO-fed rats (43) and increased PGE 2 expression in islets has been shown to result in the destruction of pancreatic islets (44) . The effect of oxidative stress, inflammation and apoptosis on b-cells and OFOinduced islet dysfunction awaits further study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we could not exclude the possibility that the metabolic alteration in OFO-fed rats might partially be related to a compromised vitamin E status, since most of the vitamin E in the oil is destroyed during the frying process and the absorption and retention of this vitamin in tissues is reduced in rats fed a frying oil diet (Liu & Huang, 1995. Recently, Oshima et al (2006) showed that the increased prostaglandin E 2 expression in the islets resulted in the destruction of pancreatic beta cells. Since significantly higher prostaglandin E 2 metabolites in plasma and urine of OFO-fed rats have been observed in our previous studies (Huang, 2003), whether the glucose intolerance observed in the OFO-fed rodents is associated with an altered prostaglandin metabolism is under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic islets were isolated by a modified collagenase digestion method as described pre- (Zhang et al, 2001;Oshima et al, 2006). Anesthetized Ephx2(Ϫ/Ϫ) and Ephx2(ϩ/ϩ) mice were sacrificed by cervical dislocation.…”
Section: Methodsmentioning
confidence: 99%